The purpose and impact of the second payment service directive on cyber security of the payment user and affected parties - Bartoszczyk-Brzoskowski, Adam (My University, 2019)
This paper evaluates the impact of the second payment service directive (PSD2) on cyber security of the payment service user. The research includes the selection of academic theory based on literature analysis of 27 academic papers, that helps to determine the purpose of said directive. Additionally, three regulatory acts (2015/2366 (PSD2), EBA/GL/2017/17, EBA/RTS/2017/02) that are the foundation of the second payment service directive are evaluated in search for specific cyber security measures influencing safety of the payment service user. Lastly, a qualitative study based on three institutions (traditional bank, third-party service provider and a legislator) affected by the scope of second payment service directive is provided, where the empirical impact of the regulation is analyzed as well as other additional implications that were a result of the policy introduction to the payment market.
Keywords: second payment service directive, PSD2, cyber security